Management of Human Resource Administration At SDN 100 And MI Darul Hikmah North Bengkulu - Izzudin, A. Tsabat; Iqbal, Moch. (JURNAL PEDAGOGY, 2024)
Each school has all processes in the management of its school administration. Especially for MI whose management is under the auspices of the Ministry of Religion, while the elementary school management is under the authority of the national education ministry. Administrative management is also adjusted to the level of existing human resources. For example, a school principal who understands the concept of good management administration will look different from one who does not understand the concept of human resource administration management. Where here human resources are very important because for a KBM to take place there must be teaching staff, school operators, treasurers, committees, etc., because there must be a decent building to support the use of good KBM and qualified ATK for the continuation of an interesting learning process, and adequate facilities are needed to support all of that. The method used by the author is qualitative where all institutions have their way of administering their schools, differences and efforts and different human resources are examples of absolute differences at a school level. The results of the study show that every education budget both in MI and in elementary school is given by the provisions or techniques that apply in education budgeting, such as the number of students, the number of teaching staff, the number of buildings that must be renovated, and so on. Therefore, each school has its tips for guaranteeing existing human resources. Human resource management is needed because the existence and progress of the school depend on school management such as principals, treasurers, teachers, operators, guards, and others.